Effect of Implementing the New Diagnostic Criteria for Noninvasive Follicular Thyroid Neoplasm with Papillary-Like Nuclear Features in King Abdulaziz University Hospital - Fatimah A. Alturkistani; Murad A. Alturkustani (Journal of King Abdulaziz University: Medical Sciences, 2023)
Pathological diagnosis of follicular variant of papillary thyroid carcinoma has high inter and intra-observer variability among expert pathologists, aff ecting prognosis and management of the disease. A recent study applying strict diagnostic criteria and long-term follow up confi rmed the indolent behavior of a subtype of these tumors. They recommended a nomenclature change to noninvasive follicular thyroid neoplasm with papillary-like nuclear features, refl ecting the low risk of adverse outcomes. We searched the pathology archives of King Abdulaziz University Hospital from 2002-2016 for all cases diagnosed with “follicular variant of papillary thyroid carcinoma”. Clinical data, and imaging fi ndings were retrospectively reviewed. Available pathology slides were reviewed using the proposed inclusion and exclusion diagnostic criteria. We confi rmed the diagnostic reproducibility of the suggested criteria. Ten out of 37 cases met the diagnostic criteria. Eight additional patients could have had their diagnosis modifi ed if sufficient tissue samples were available. Follow up data confi rmed the indolent behavior in these cases with no recurrence or adverse outcome. We concluded that application of the new diagnostic criteria for this subtype is reasonable and has major ramifi cations for the diagnosis and management as this will spare unnecessary thyroidectomies, radioactive iodine therapy, and their complications.